Based on the given information, it seems that Jeremy is performing an operation on the values of x and recording the corresponding values of y.
From the given table, it can be observed that there is a consistent pattern in the values of y. In fact, the values of y appear to be increasing by 8 for every increase of 2 in x.
To generalize the pattern observed, we can write the relationship between x and y as follows:
y = 3x + 2
Using this formula, we can calculate the value of y for any given value of x. For example, if x = 10, then using the formula:
y = 3(10) + 2
y = 32
So, when x = 10, the corresponding value of y would be 32.
jeremy performs the same operation on 4 values for x he records each value in a table as shown below x2,4,6,8y5,13,21,29
7 answers
write it as an expression
The relationship between x and y can be expressed as:
y = 3x + 2
y = 3x + 2
wrong
Apologies for the confusion. Let me try again.
The relationship between x and y can be expressed as:
y = 2x + 3
The relationship between x and y can be expressed as:
y = 2x + 3
its one of these y=x+3, y=3x-1, y=2x+1 and y=4x-3
Apologies for the mistake. Thank you for providing the correct options.
Based on the given data points in the table:
x | 2 | 4 | 6 | 8
y | 5 | 13 | 21 | 29
We can use the method of substitution to determine the correct expression:
1. If we use y = x + 3:
- For x = 4, y = 7 (not 13 as given)
- Therefore, this expression does not fit the given data points.
2. If we use y = 3x - 1:
- For x = 4, y = 11 (not 13 as given)
- Therefore, this expression does not fit the given data points.
3. If we use y = 2x + 1:
- For x = 4, y = 9 (not 13 as given)
- Therefore, this expression does not fit the given data points.
4. If we use y = 4x - 3:
- For x = 4, y = 13
- All other data points also match this expression.
- Therefore, this expression fits the given data points.
Hence, the correct expression is:
y = 4x - 3
Based on the given data points in the table:
x | 2 | 4 | 6 | 8
y | 5 | 13 | 21 | 29
We can use the method of substitution to determine the correct expression:
1. If we use y = x + 3:
- For x = 4, y = 7 (not 13 as given)
- Therefore, this expression does not fit the given data points.
2. If we use y = 3x - 1:
- For x = 4, y = 11 (not 13 as given)
- Therefore, this expression does not fit the given data points.
3. If we use y = 2x + 1:
- For x = 4, y = 9 (not 13 as given)
- Therefore, this expression does not fit the given data points.
4. If we use y = 4x - 3:
- For x = 4, y = 13
- All other data points also match this expression.
- Therefore, this expression fits the given data points.
Hence, the correct expression is:
y = 4x - 3